TRANSIENT OSTEOPOROSIS SECONDARY TO TENOFOVIR - Yi, Cheong Wei; Noor, Sharifah Noor Adrilla binti Long Mohd; Rajoo, Subashini (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Tenofovir is the first-line antiviral therapy for chronic hepatitis B, however, long-term use may induce osteoporosis. This is a case of a patient who developed transient osteoporosis after chronic use of tenofovir. CASE A 57-year-old male with chronic Hepatitis B on tenofovir, presented with a 2-year history of progressive limb weakness, myalgia, and weight loss of 6 kg. He sustained a low impact fracture of his left ankle 2014 and incidentally noted a right pelvic fracture through an MRI of the pelvis in 2017. His blood parameters were normal including serum calcium, phosphate, vitamin D and parathyroid hormone levels. First BMD examination in 2018 showed severe osteoporosis with a T-score of – 4.9 and -4.7 for the distal one-third of the left forearm and spine respectively. Serial BMD examination one year later, showed the persistence of severe osteoporosis with a T-score of -3.4, -3.3 at the hip and spine respectively. Moreover, there was a worsening of T-score to -6.0 at the distal one-third of the forearm. He was then initiated on oral bisphosphonate. Additional proximal myopathy workup including FDG-PET scan, CECT Thorax, abdomen and pelvis and muscle biopsy were all normal. EMG showed diffuse neurogenic with secondary myogenic changes, suggestive of a metabolic aetiology. Thus, tenofovir was switched to entecavir and lamivudine after all other metabolic causes were ruled out. Osteoporosis treatment with oral bisphosphonate and vitamin D supplements was continued. The latest BMD examination in 2024 showed a markedly improved T-score and resolution of his osteoporosis. CONCLUSION Tenofovir may lead to osteoporosis development through directly altering osteoclasts and/or osteoblasts activity. Furthermore, literature showed it can also affect the proximal renal tubules and vitamin D metabolism. Hence, close monitoring of tenofovir plasma concentrations coupled with renal and bone function is essential. Early detection, diagnosis, and treatment of osteoporosis induced by these drugs should be emphasized.